Psychological abuse as a cause for disinheritance of children and descendants - Díaz Alabart, Silvia (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This text examines the disinheritance of children and descendants due to mistreatment or insults (art.853, 2nd CC) with special attention to the jurisprudential interpretation of the SC of the article, which leaves behind the traditional restrictive interpretation and includes psychological mis-treatment as a type of mistreatment and goes into the requirements that must be fulfilled for it to be considered a just cause for disinheritance.